2022
DOI: 10.1128/aac.00621-22
|View full text |Cite
|
Sign up to set email alerts
|

Mutation to ispA Produces Stable Small-Colony Variants of Pseudomonas aeruginosa That Have Enhanced Aminoglycoside Resistance

Abstract: Pseudomonas aeruginosa is a major pathogen in burn wound infections. We present one of the first reports of small-colony variant (SCV) emergence of P. aeruginosa , taken from a patient under aminoglycosides for a persistent burn wound infection. We confirm the causative role of a single ispA mutation in SCV emergence and increased aminoglycoside resistance. IspA is involved in the synthesis of ubiquinone, providing a possible link between electron tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…S6), all of which have been described previously in the context of chronic CF infection (13,48). These findings, taken with a recent report showing SCV emergence in an infected burn patient (49), suggest that while the niches are fundamentally distinct, evolutionary pathways toward infection are similar between acute (i.e., burn) and chronic (i.e., CF) settings. Additionally, while sampling in CF studies has been performed over many decades, it is apparent that significant adaptation occurs in the first 2 to 3 years (50), which is similar to the time frame assessed in this study, and further highlights the rapid nature of P. aeruginosa reprogramming for persistence in the human host.…”
Section: Discussionsupporting
confidence: 75%
“…S6), all of which have been described previously in the context of chronic CF infection (13,48). These findings, taken with a recent report showing SCV emergence in an infected burn patient (49), suggest that while the niches are fundamentally distinct, evolutionary pathways toward infection are similar between acute (i.e., burn) and chronic (i.e., CF) settings. Additionally, while sampling in CF studies has been performed over many decades, it is apparent that significant adaptation occurs in the first 2 to 3 years (50), which is similar to the time frame assessed in this study, and further highlights the rapid nature of P. aeruginosa reprogramming for persistence in the human host.…”
Section: Discussionsupporting
confidence: 75%
“…SCVs of a variety of other bacterial species, such as Staphylococcus aureus , Escherichia coli , Burkholderia pseudomallei , Burkholderia cepacia , Vibrio cholerae , and Neisseria gonorrhoeae , have been recovered from clinical samples, e.g., from the respiratory tract, blood, and soft tissues (reviewed in reference 19 ). In recent years, many efforts to gain new insights into the molecular mechanisms underlying the switch to a small-colony variant phenotype have been made ( 20 24 ). Various studies have demonstrated that the SCV phenotype is often, but not exclusively, associated with elevated intracellular levels of the second messenger bis-(3′-5′)-cyclic dimeric GMP (c-di-GMP) ( 14 , 23 , 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pitton et al had confirmed the causative role of a single ispA mutation in SCV emergence and increased aminoglycoside resistance. IspA is involved in the synthesis of ubiquinone, providing a possible link between electron transport and SCV formation in P. aeruginosa (Pitton et al, 2022). Kleinert et al inserted the IS256 sequence into the wild strain and found a very rapid reversion to the wild type that resembled the fast reversion of clinical SCVs (Kleinert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Melissa et al confirmed the causative role of a single ispA mutation in P. aeruginosa SCV emergence and increased aminoglycoside resistance. IspA is involved in the synthesis of ubiquinone, providing a possible link between electron transport and SCV formation in P. aeruginosa (Pitton et al, 2022).…”
Section: Introductionmentioning
confidence: 99%